Repercusiones sociales - laborales en pacientes diagnosticados con VIH, Hospital Sagrado Corazón De Jesús Quevedo, periodo enero - abril 2023. - Yumbo Moposita, Neyser Adrian (2023)
People with HIV can face a variety of challenges, such as social isolation and discrimination. Often, the stigma associated with the condition can cause individuals to feel ashamed or rejected by their community, often leading to the loss of friends, family, and support networks, which in turn tends to have an impact on the mental and emotional health of individuals. Objective: To identify the social and labor repercussions that are generated from the diagnosis of HIV in the patients of the Hospital Sagrado Corazón de Jesús Quevedo, during the period from January to April 2023. Methodology: Descriptive, quantitative research level, non-experimental and cross-sectional design, population made up of 21 patients living with HIV, while the technique was the survey validated by experts. Results: The sociocultural factors that prevailed were the age of 26 to 35 years, the masculine gender, the heterosexual sexual orientation, the singles, the part-time job, the secondary study, the time of two to four years of antiretroviral use. . Subjects between the ages of 18 and 25, whether heterosexual or homosexual, never felt isolated and stated that others are not afraid of them. Adding to this, bisexuals between the ages of 26 and 35 almost never fear that people will judge them for their disease and claim to receive the same treatment in public spaces. In turn, patients between 18 and 25 years of age in heterosexuals and homosexuals (4), did not experience changes in their work history. However, subjects between the ages of 26 and 35 (2), both bisexual and heterosexual, suffered discrimination when seeking employment. This age group was also affected by the support of their peers upon learning of their pathology (4). Heterosexuals (3) and homosexuals (3) over 18 years of age have not suffered violence or harassment due to the diagnosis. Finally, heterosexuals between the ages of 36 and 45 appreciated that the diagnosis prevented them from carrying out their work effectively. Conclusion: It was concluded that in the majority of the population there is no repercussion, only having a small percentage that suffered work-social repercussions that affect patients mentally and emotionally. Keywords: HIV, Discrimination, Stigmatization, Labor repercussions, Social factors